Hepatic Hydatid Disease Causing Gastric Ulcer as a Rare Complication - Eunae Cho; Sang Soo Shin; Ga Eon Kim (대한영상의학회지, 2019)
Hydatid disease in humans is a parasitic disease typically caused by the larvae of Echinococcus granulosus. Although the disease can occur in any body part, it most frequently affects the liver. Hydatid disease is usually diagnosed incidentally and presents with various types of cystic lesion in the infected anatomical locations. Among the many potential complications of hepatic hydatid cysts, including rupture, infection, biliary communication, and peritoneal seeding, spontaneous rupture of the cyst into the hollow viscera is exceptionally rare and has been reported in less than 0.5% of cases. We report the case of a patient with hepatic hydatid disease complicated by spontaneous rupture into stomach causing gastric ulcer and peritoneal seeding.